Etnososio : Pembelajaran Sosiologi Berbasis Kearifan - Abdurrohman, Abdurrohman; Suastra, I Wayan; Putu Arnyana, I Bagus; Herlina, Nurlaili (Educatio, 2024)
This research aims to examine the meanings embedded in the ritual of "perang topat" as local wisdom of the Sasak tribe that can be utilized as a learning resource for sociology at the high school level or equivalent. Sociology, as a branch of Social Sciences, can utilize this local wisdom to enrich understanding while assisting students in comprehending sociology learning themes. This study employs a Descriptive Qualitative research design. Data collection is conducted through non-participant observation, in-depth interviews, and documentation. Data analysis utilizes interactive techniques. The research findings indicate that the local wisdom of the "perang topat" ritual can serve as a sociology learning resource as it is relevant to one of the sociology learning themes in the tenth-grade curriculum, namely social phenomena in multicultural societies. Moreover, utilizing the "perang topat" ritual as a learning resource is a contextual approach that can aid students in understanding sociology topics by directly observing real-life events. By utilizing the local wisdom of "perang topat" as a learning resource, creative, innovative, and enjoyable sociology learning experiences can be created